Media Language: Projection and Interpretation - Surendra Singh Vaidwan (Jaipur: Paradise Publishers, 2021)
Media is the collective communication outlets or tools that are used to store and deliver information or data.
Includes Bibliographic references and index.
Keywords: Media--Mass Media--Broadcast Media--Media Writing--Sign Language--Video Interpreting Service